1978
DOI: 10.1104/pp.62.4.642
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Effects on Soybean (Glycine max [L.] Merr. cv. Wells) Free Amino Acid Pools during Germination

Abstract: The free amino acid concentrations in cotyledons and axes of soybean (Glycine max IL.I Merr. cv. Wells) seedlings were determined by automated single column analysis after germiation at 10 and 23 C. After 5 days germination at 10 C, glutamate and aspartate were in high concentration in both cotyledons and axes (38 and 24% of total free amino acids recovered, respectively), whereas the concentrations of their amide derivatives, asparagine and glutamine, were iow in cotyledons (4.4%) and high in axes (21%). In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Moreover, Duke et al (1978) found high glutamic acid concentrations in both cotyledons and axes of soybean seedling after 5 days of germination at 10°C.…”
Section: Gaba Concentrations In Rice Grains Using Germination Methodsmentioning
confidence: 96%
“…Moreover, Duke et al (1978) found high glutamic acid concentrations in both cotyledons and axes of soybean seedling after 5 days of germination at 10°C.…”
Section: Gaba Concentrations In Rice Grains Using Germination Methodsmentioning
confidence: 96%
“…imbibition and germination (8,9,11,21,22). This may be due to incorporation of cytosol pools of these enzymes into mitochondria during hydration, de novo synthesis, or to an increase in structural integrity of mitochondria during hydration.…”
Section: Results and Discussion Preliminary Observations Of Imbibitiomentioning
confidence: 99%
“…All dehydrogenase and dehydrogenase-linked enzyme assays were conducted spectrophotometrically measuring the reduction of NAD(P)+ or the oxidation of NAD(P)H at 340 nm with a Pye Unicam SP8-100 double-beam spectrophotometer at 30 C. Except for the assay buffer (100 mm Hepes), assays are as previously described for GDH2 and MDH (7), NADP-ICDH and G6P-DH (8), and GOT (9). Assays for AK were coupled to G6P-DH and reaction mixtures (2 ml) contained, in order of addition and in final concentration: 75 from horse heart (Sigma), reduced with ascorbate and dialyzed with 1,000 volumes H20 for 18 h at 5 C; A5w/Aw = >20), and 50 A1 enzyme preparation to a final volume of 1.0 ml.…”
mentioning
confidence: 99%
“…Although there have been a number of reports indicating that growing seedlings may contain such pools (e.g. 4,8) these may be subject to other interpretations. It seems likely that the methods employed here could be applied with little or no modification to other tissues in order to establish the general existence and possible function of peptide pools in plant tissues.…”
Section: Peptide and Amino Acid Pool Sizesmentioning
confidence: 99%